Crohn's disease presenting as enterovesical fistula. (18th November 2013) - Cullis, Paul; Mullassery, Dhanya; Baillie, Colin; Corbett, Harriet
Abstract : Enterovesical fistulae in Crohn's disease are relatively rare. We present the first report of a child presenting with an enterovesical fistula as the initial presentation of Crohn's disease. Management comprises of timely diagnosis, and treatment involving surgical resection with adjunctive medical management including immunomodulators. This case highlights the need to be aware of the rare but important occurrence of Crohn's enterovesical fistula as a cause for urinary symptoms in a child with inadequate weight gain.